Taxonomic, bioacoustic and faunistic data on a collection of Tettigonioidea from Eastern Congo (Insecta: Orthoptera) - Heller, Klaus-Gerhard; Hemp, Claudia; Liu, Chunxiang; Volleth, Marianne (Zootaxa, 2014)
During a 14-day excursion in March 1990, 28 species of tettigonioids were found at Irangi (1º54’S, 28º27’E), ca.100 km north west of Bukavu at Lake Kivu (Democratic Republic of the Congo, formerly Zaire), and at other localities near Bukavu. One species —Arantia (Arantia) gracilicercata Heller sp. n. — is new to science, another one—Pantecphyllus helleri Schmidt et al. 2004—was already described as new in a generic revision. All our specimens of the morphologically quite diverse and sexually dimorphic phaneropterine genus Arantia were studied using molecular methods. We propose a new subgenus Arantia (Euarantia) Heller subgen. n. based on relative tegmen width. Songs and stridulatory organs were studied in 9 species. Two phaneropterines, Horatosphaga leggei and Pardalota asymmetrica, showed remarkable calling songs lasting more than 10 s and produced by quite complicated stridulatory movements. The song of the large phaneropterine Zeuneria biramosa is noteworthy because of its unusually low carrier frequency of 3.7 kHz. Based on the examination of other specimens and species, some taxonomic changes are proposed (Phaneropteridae Burmeister, 1838 stat. rev.; Afromecopoda monroviana (Karsch, 1886) stat. rev.; Leproscirtus ebneri Karny, 1919, syn. n., Leproscirtus karschi Karny, 1919, syn. n., Leproscirtus granulosus aptera Karny, 1919, syn. n., all synonyms of Leproscirtus granulosus (Karsch, 1886); Lanistoides Sjöstedt, 1913 stat. rev.; Plastocorypha cabrai Griffini, 1909 stat. n.).